Cuprous oxide core-shell composite material, and preparation method and application thereof
By forming a continuous and dense shell of materials such as polydopamine, silica, alumina, zinc oxide, or titanium oxide on the surface of nano-Cu2O, the problem of easy oxidation of nano-Cu2O in humid environments is solved, achieving long-term stability and activity retention, and providing additional functions.
Patent Information
- Application Number
- CN202611191423.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-08-07
AI Technical Summary
Existing technologies make it difficult to form a continuous and dense protective shell on the surface of nano-Cu2O without damaging the core of the nano-Cu2O, which makes nano-Cu2O easy to oxidize in humid environments, affecting its stability and activity.
Materials such as polydopamine, silica, alumina, zinc oxide, or titanium oxide are used as the shell layer. A continuous and dense shell layer is formed at a temperature not exceeding 150°C using mild liquid-phase methods such as PDA self-polymerization, sol-gel method, or atomic layer deposition, avoiding high-temperature calcination.
It achieves improved long-term stability of nano-Cu2O in room temperature air atmosphere, with core activity retention rate exceeding 95%, shell layer blocking oxygen and moisture penetration, and endows additional functions such as ultraviolet shielding or antibacterial properties.
Smart Images

Figure CN122682508B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of nanocomposite materials technology, specifically to an antioxidant-coated cuprous oxide core-shell composite material, its preparation method, and its application. Background Technology
[0002] Nano-cuprous oxide (Cu2O) exhibits broad application prospects in catalysis, sensors, biomedicine, and environmental remediation due to its unique semiconductor properties, excellent photocatalytic activity, and antibacterial properties. However, nano-Cu2O is readily oxidized to CuO or basic copper salts in air (especially in humid environments), leading to irreversible degradation of its intrinsic properties. Existing research indicates that surface ligand modification (such as PVP) can improve its stability to some extent, but the protective capabilities of such organic monolayers are limited, making it difficult to meet the application requirements for long-term storage or harsh environments.
[0003] In the field of nanomaterials, coating an active core with an inert protective shell (such as SiO2 or C) is a common strategy to improve stability. However, applying this strategy to chemically sensitive nano-Cu2O faces significant challenges: conventional coating methods, such as the alkaline Stöber process commonly used to prepare SiO2 shells, directly dissolve or oxidize the Cu2O core in their strongly alkaline environment, leading to the failure of core-shell structure preparation. Therefore, there is an urgent need to develop a mild and uniform coating technique compatible with the fragile Cu2O nanocore to obtain practical, highly stable nano-Cu2O composite materials.
[0004] In the prior art, Chinese patent CN202511234252 discloses a method for encapsulating cuprous oxide red pigment with silica. This method involves surface modification and sol-gel coating, followed by high-temperature calcination at 800-1000℃ in a hydrogen-argon mixed atmosphere to obtain a dense shell. This method is not only energy-intensive and requires demanding equipment, but the high-temperature treatment also severely damages the grain size and surface organic ligands of Cu2O, leading to a significant decrease in its intrinsic activities (such as antibacterial and catalytic properties). Another Chinese patent CN202111326913 uses aluminum-containing compounds to modify or adsorb onto the Cu2O surface, but the resulting surface layer is usually a discontinuous island or sub-monolayer structure, failing to form a truly physically isolated dense shell, thus limiting its antioxidant protection effect. Therefore, developing a coating technology that requires no high-temperature post-treatment, can gently form a complete dense shell in the liquid phase without damaging the highly active nano-Cu2O core, is a key bottleneck for technological breakthroughs in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a cuprous oxide core-shell composite material with a continuous and dense shell layer on the surface. At the same time, this invention also provides a method for preparing a cuprous oxide core-shell composite material that does not require high-temperature calcination, does not damage the highly active nano-cuprous oxide core, and can form a continuous and dense protective shell layer on the surface of cuprous oxide.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a cuprous oxide core-shell composite material with a continuous and dense shell layer covering its surface, the cuprous oxide core-shell composite material comprising a core and a continuous and dense shell layer covering the surface of the core; The core is nano-cuprous oxide; The thickness of the shell layer is 1-50 nm, and the composition of the shell layer is at least one of polydopamine, silicon dioxide, aluminum oxide, zinc oxide, and titanium dioxide. The average particle size of the nano-cuprous oxide is 20-180 nm, and the shell is formed under conditions not exceeding 150 °C and not strongly alkaline.
[0007] The cuprous oxide core-shell composite material of this invention uses nano-cuprous oxide as the core, with a continuous and dense shell layer on its surface. The shell layer is composed of at least one of polydopamine, silica, alumina, zinc oxide, and titanium dioxide. These materials can all be formed by mild liquid-phase methods (such as PDA self-polymerization, sol-gel method, chemical precipitation method, or atomic layer deposition) at temperatures not exceeding 150°C, avoiding the damage to the core caused by high-temperature calcination. Because no heat treatment above 150°C is performed throughout the process, the grain size, morphology, and surface organic ligands of the nano-Cu₂O are completely preserved, and the antibacterial activity retention rate of the core can exceed 95%. Simultaneously, the continuous and dense shell layer effectively blocks the penetration of oxygen and moisture, ensuring that no CuO is formed after 12 months of storage in room temperature air, significantly improving long-term stability. Furthermore, the shell layer can be used to impart additional functions to the composite material by selecting different materials; for example, a TiO₂ shell layer can provide UV shielding, while a ZnO shell layer can enhance antibacterial durability.
[0008] The thickness of the shell layer is 1-50 nm, including but not limited to any selection or any combination of two of the following: 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm. Selecting a shell layer within this thickness range ensures that the shell layer is continuous and dense, effectively blocking oxygen and moisture, while avoiding excessive coverage and obscuring of the active sites in the core.
[0009] The shell layer can be composed of at least one of polydopamine, silica, alumina, zinc oxide, and titanium dioxide. For example, the shell layer can be prepared using one of polydopamine, silica, alumina, zinc oxide, and titanium dioxide, or it can be composed of two or more of these materials. Preferably, the shell layer is composed of polydopamine and silica. More preferably, the polydopamine coats the core surface, and the silica coats the outer layer of the polydopamine. When the shell layer is a composite layer of polydopamine and silica, the polydopamine acts as an anchoring layer directly coating the nano-cuprous oxide surface, and the silica coats the outer layer of the polydopamine. Polydopamine has strong adhesion and can form a uniform film on any surface. Its catechol groups can induce the hydrolysis and condensation of tetraethyl orthosilicate (TEOS), thereby forming a dense SiO2 outer layer in situ. This composite shell structure fully leverages the interfacial bridging effect of PDA and the high density of SiO2, resulting in a controllable, uniform, continuous, and pinhole-free shell thickness with the best anti-oxidation effect.
[0010] The thickness of the shell can have different preferred ranges depending on the shell composition, specifically: When the shell component is polydopamine, the shell thickness is preferably 5-12 nm, more preferably 8 nm.
[0011] When the shell is a composite layer of polydopamine and silica, the thickness of the shell is preferably 5-12 nm, wherein the thickness of the polydopamine anchoring layer is <5 nm, and the thickness of the silica outer layer is controlled by the concentration of tetraethyl orthosilicate.
[0012] When the shell is made of aluminum oxide and prepared by atomic deposition, the shell thickness is preferably 1.5~7.5 nm.
[0013] When the shell is made of aluminum oxide and prepared by chemical precipitation, the shell thickness is preferably 5-15 nm.
[0014] When the shell is zinc oxide, the shell thickness is preferably 4~15 nm, and the zinc oxide shell of this thickness also has a synergistic antibacterial function.
[0015] When the shell is titanium dioxide, the shell thickness is preferably 3~15 nm, and the titanium dioxide shell of this thickness can expand the application of ultraviolet photocatalysis.
[0016] In the cuprous oxide core-shell composite material of the present invention, the nano-cuprous oxide serving as the core can be a common nano-cuprous oxide material in the prior art. Preferably, in the cuprous oxide core-shell composite material of the present invention, the nano-cuprous oxide serving as the core is a self-made ultrafine nano-cuprous oxide. Specifically, the average particle size of the nano-cuprous oxide is 20-180 nm, the surface of the nano-cuprous oxide has a modification layer formed by chemical modification with organic ligands, the shell layer covers the modification layer of the nano-cuprous oxide, and the nano-cuprous oxide satisfies the following: D 90 / D 10 The ratio is 1.2 to 5.0. The D 90 The particle size corresponding to a cumulative particle size distribution percentage of 90% for the aforementioned nano-cuprous oxide is defined as follows: The D 10 This refers to the particle size corresponding to a cumulative particle size distribution percentage of 10% for the nano-cuprous oxide.
[0017] In the aforementioned self-made nano-cuprous oxide, the average particle size of the nano-cuprous oxide is 20-180 nm, for example, any value or range of any two of the following: 20 nm, 50 nm, 80 nm, 120 nm, 150 nm, and 180 nm. The average particle size described in this invention is D. 50 That is, the ultrafine nano-cuprous oxide particles are arranged according to their size, and the particle size is accumulated to 50% when the particles are of different sizes.
[0018] In the self-made nano-cuprous oxide described above, its D 90 / D 10 The ratio is 1.2 to 5.0, for example, including but not limited to D. 90 / D 10 The range can be any point value or any two points, such as 1.2, 1.32, 1.5, 1.6, 2.0, 2.26, 2.58, 2.61, 2.67, 2.78, 3.29, 3.70, 3.8, 4.0, 4.2, 4.5, 4.8, 5.0. Preferably, the D... 90 / D 10 The ratio is 1.3 to 3.8.
[0019] When the core uses nano-cuprous oxide as described above, the particle size distribution range ensures that the core particles are uniform in size, without the problem of incomplete shell coverage caused by excessively large particles, and without the defects of excessively high surface energy and easy agglomeration caused by excessively small particles. With the addition of surface organic ligand modification, the growth rate deviation of the shell on the core surface can be small, ensuring batch consistency of the core-shell structure.
[0020] Preferably, in the self-made nano-cuprous oxide as described above, the organic ligand in the modified layer is selected from at least one of poloxamer, Tween, sodium citrate, PVP, SDS, and CTAB. The organic ligand can be a single component or a compound system of poloxamer, Tween, sodium citrate, PVP, SDS, and CTAB. For example, poloxamer can be poloxamer 407, Tween can be Tween-80, and PVP can be PVP-K30.
[0021] Preferably, the nano-cuprous oxide is composed of cubic Cu2O.
[0022] Preferably, the nano-cuprous oxide particles are spherical, near-spherical, or polyhedral.
[0023] Preferably, the specific surface area of the nano-cuprous oxide is 15~50 m². 2 / g. The specific surface area of the nano-cuprous oxide can be, for example, 15m². 2 / g、25m 2 / g, 32m 2 / g、40m 2 / g, 50m 2 Any value in / g or any range of two points can provide more shell anchoring points for high specific surface area nano-cuprous oxide, thereby improving the interfacial bonding strength.
[0024] The nano-cuprous oxide produced in this invention, when stored at room temperature and in air for 6 months, showed no CuO characteristic peaks in XRD analysis and remained orange-red in color.
[0025] Secondly, the present invention provides a preparation method with mild reaction conditions, which does not require high-temperature calcination and can form a continuous and dense protective shell on the surface of nano-cuprous oxide. To achieve this objective, the technical solution adopted by the present invention is as follows: When the shell is polydopamine, the preparation method of the nano-cuprous oxide core-shell composite material includes the following steps: (1-1) The nano-cuprous oxide is uniformly dispersed in a solvent to form a premixed solution; (1-2) Add dopamine hydrochloride to the premixed solution formed in step (1-1), wherein the mass ratio of dopamine hydrochloride to nano cuprous oxide is (0.5-3):1; (1-3) Stir the reaction at 20-60℃ in air or an inert atmosphere for 6-24 hours to obtain the initial product of cuprous oxide core-shell composite material; (1-4) The initial product of cuprous oxide core-shell composite material obtained in step (1-3) is centrifuged, washed and dried to obtain cuprous oxide core-shell composite material.
[0026] When the shell is polydopamine, the solvent in step (1-1) can be, for example, a Tris buffer solution with a pH of 8-8.5, or a mixed solvent of water and alcohol. When a mixed solvent of water and alcohol is chosen, the alcohol can be, for example, ethanol. The volume ratio of water to alcohol is not particularly limited, and can be, for example, arbitrarily selected from 1:1, 1:2, 1:3, 2:1, 3:1, etc. The concentration of nano-cuprous oxide in the premixed solution in step (1-1) is not particularly limited, and can be 1~10 g / L, for example, including but not limited to any combination of 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, or any two of these values.
[0027] In steps (1-2), the mass ratio of dopamine hydrochloride to nano-cuprous oxide can be any value or a range of any two of the following: 0.5:1, 1:1, 2:1, 3:1. The ratio of dopamine hydrochloride to nano-cuprous oxide can control the thickness of the dopamine hydrochloride shell. If the ratio of dopamine hydrochloride is too low, the shell will be too thin and unable to completely block oxygen; while if the ratio of dopamine hydrochloride is too high, the PDA layer will be too thick, hindering the exposure of the core active sites.
[0028] The reaction temperature in steps (1-3) can be selected, for example, 20℃, 30℃, 40℃, 50℃, or 60℃, and the reaction time can be selected, for example, 6h, 12h, 18h, or 24h. The method uses mild reaction conditions, which can avoid excessive oxidation of dopamine to produce insoluble aggregates and ensure the uniformity of the shell.
[0029] In the preparation method of polydopamine described in this invention, dopamine undergoes oxidative self-polymerization under weakly alkaline conditions. PDA molecules are adsorbed onto organic ligands on the surface of Cu2O through π-π interactions and hydrogen bonds, gradually forming a cross-linked network structure. Continuous coating can be achieved without additional cross-linking agents, and the reaction process does not involve strong acids or bases, thus not damaging the Cu2O core.
[0030] When the shell layer is a composite layer of polydopamine and silica, the preparation method of the nano-cuprous oxide core-shell composite material includes the following steps: (2-1) Disperse the nano-cuprous oxide uniformly in the solvent to form a premix; (2-2) Add dopamine hydrochloride to the premixed solution formed in step (2-1), wherein the mass ratio of dopamine hydrochloride to nano cuprous oxide is (0.25-1.5):1, and react at room temperature for 30-60 minutes to obtain an intermediate solution; (2-3) Add an ethanol solution of tetraethyl orthosilicate to the intermediate solution obtained in step (2-2), control the concentration of tetraethyl orthosilicate after addition to 1.0~2.0 M, and continue to stir the reaction at 20-60℃ for 6-24h to obtain the initial product of cuprous oxide core-shell composite material. (2-4) The initial product of cuprous oxide core-shell composite material obtained in step (2-3) is centrifuged, washed and dried to obtain cuprous oxide core-shell composite material.
[0031] When the shell is a composite layer of polydopamine and silica, the nano-cuprous oxide core-shell composite material of this application is prepared by the method described above. In the method, the phenolic hydroxyl groups on the surface of the thin PDA layer serve as heterogeneous nucleation sites, reducing the activation energy of TEOS hydrolysis and condensation, so that SiO2 grows in situ on the core surface instead of homogeneous nucleation, solving the problem that SiO2 cannot be uniformly coated when Cu2O is oxidized under strong alkaline conditions in the traditional Stober method without an anchoring layer.
[0032] In the method described above, the solvent in step (2-1) can be, for example, a Tris buffer solution with a pH of 8-8.5, or a mixed solvent of water and alcohol. When a mixed solvent of water and alcohol is selected, the alcohol can be, for example, ethanol. The volume ratio of water to alcohol is not particularly limited, and can be, for example, arbitrarily selected as 1:1, 1:2, 1:3, 2:1, 3:1, etc. The concentration of nano-cuprous oxide in the premixed solution in step (2-1) is not particularly limited, and can be 1~10 g / L, for example, including but not limited to any combination of 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, or any two of these values.
[0033] In step (2-2), the mass ratio of dopamine hydrochloride to nano-cuprous oxide is (0.25-1.5):1, for example, it can be any value or any range of two points from 0.25:1, 0.5:1, 1:1, 1.5:1. This amount only forms a PDA anchoring layer of a certain thickness (generally <5nm) to avoid the subsequent SiO2 shell layer being too thick.
[0034] In step (2-3), the concentration of tetraethyl orthosilicate after addition is 1.0~2.0 M. For example, any value or any two of 1.0 M, 1.2 M, 1.5 M, and 2.0 M can be selected. This concentration range can control the SiO2 shell to have a suitable thickness and density: if the concentration is too low (e.g., below 1.0 mol / L), the shell will be too thin or discontinuous, and the coating integrity will be insufficient; if the concentration is too high (e.g., above 2.0 mol / L), the reaction rate will be too fast, which will easily produce free SiO2 particles or the shell will be too thick, affecting the exposure of the core active sites.
[0035] When the shell is alumina, the preparation method of the nano-cuprous oxide core-shell composite material includes the following steps: Using an atomic deposition apparatus, nano-cuprous oxide is placed in a reaction chamber, and trimethylaluminum and water are used as precursors. The deposition is carried out for 10 to 50 cycles at 80 to 120°C to obtain a cuprous oxide core-shell composite material.
[0036] When the shell is alumina, it can be prepared by atomic deposition. During the preparation process, 10 to 50 deposition cycles are performed at 80–120°C. The reaction temperature can be selected as 80°C, 100°C, or 120°C, and the number of cycles can be selected as 10, 20, 30, 40, or 50. The self-limiting surface reaction characteristics of ALD enable shell growth with atomic precision. Each deposition cycle has a thickness of approximately 0.1–0.3 nm, ultimately forming a dense Al₂O₃ layer with a thickness of 3–15 nm. Furthermore, the reaction temperature is below 120°C, which does not damage the organic ligand modification layer of the Cu₂O core.
[0037] When the shell is alumina, the nano-cuprous oxide core-shell composite material can also be prepared by the following methods: (4-1) Disperse nano-cuprous oxide in a solvent to form a dispersion; (4-2) Add aluminum isopropoxide solution in isopropanol to the dispersion in step (4-1) so that the molar ratio of Al to Cu2O is (0.5~4.0):1; (4-3) Under an inert atmosphere and at 20-50℃, slowly add an alkaline solution to adjust the pH to 6.5-7.5, controlling the dropping rate to 0.1-0.5 mL / min, so that Al 3+ A uniform hydrolysis of Cu2O surface generates an Al(OH)3 gel layer; (4-4) Continue stirring for 2-6 hours, centrifuge, wash, and dry to obtain the Al(OH)3 coated intermediate; (4-5) The intermediate obtained in step (4-4) is heat-treated at 120-150℃ for 1-2 hours under a nitrogen atmosphere to dehydrate Al(OH)3 and transform it into a continuous and dense amorphous Al2O3 shell, thus obtaining the cuprous oxide core-shell composite material.
[0038] When the shell is alumina, it can also be prepared by chemical precipitation, as described above. The solvent used in step (4-1) can be, for example, isopropanol or ethanol, and the concentration of nano-cuprous oxide in the dispersion of step (1) can be 5-20 g / L.
[0039] In step (4-2), the molar ratio of Al to Cu2O is (0.5~4.0):1, including but not limited to any value or any two values from 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, and 4:1. This ratio range can control the Al2O3 shell thickness between 5 and 15 nm: when the molar ratio of Al to Cu2O is (0.5~4.0):1, it can ensure that Al... 3+ A continuous and dense Al(OH)3 gel layer is formed by uniform hydrolysis on the Cu2O surface with sufficient supersaturation. After low-temperature dehydration, a complete Al2O3 shell without pinholes is obtained. If the Al ratio is too low (e.g., below 0.5:1), the amount of Al(OH)3 generated by hydrolysis is insufficient to cover the entire core surface, resulting in a discontinuous shell. If the Al ratio is too high (e.g., above 4.0:1), the hydrolysis reaction is too vigorous, which can easily produce free Al(OH)3 precipitates or an excessively thick shell, affecting the exposure of the active sites in the core.
[0040] In step (4-3), the pH value needs to be adjusted to 6.5–7.5, for example, 6.5, 7.0, or 7.5. The alkaline solution can be ammonia or NaOH solution, and the rate of addition of the alkali needs to be controlled at 0.1–0.5 mL / min, for example, 0.1 mL / min, 0.2 mL / min, 0.3 mL / min, 0.4 mL / min, or 0.5 mL / min. A slightly neutral condition can prevent Cu₂O from dissolving and oxidizing in an alkaline environment, and a slow addition can ensure the stability of Al. 3+ Uniform hydrolysis on the nucleus surface avoids excessively high local concentrations that could lead to the precipitation of free Al(OH)3.
[0041] The stirring time in step (4-4) can be any of 2h, 4h, 6h, etc.; the heat treatment temperature in step (4-5) can be, for example, 120℃, 135℃, 150℃, and the time can be, for example, 1h, 1.5h, 2h. This low-temperature heat treatment only dehydrates Al(OH)3 and converts it into amorphous Al2O3, without causing Cu2O grain growth or oxidation.
[0042] When aluminum oxide is coated onto the surface of nano-cuprous oxide using the aforementioned chemical precipitation method, the controllable hydrolysis under neutral and weakly alkaline conditions avoids the high alkalinity risk of traditional aluminum salt hydrolysis, and the subsequent low-temperature dehydration avoids damage to the core caused by high-temperature calcination.
[0043] When the shell is zinc oxide, the preparation method of the nano-cuprous oxide core-shell composite material includes the following steps: (5-1) Disperse nano-cuprous oxide in a solvent to form a dispersion; (5-2) Add zinc acetate dihydrate to the dispersion in step (5-1) so that the molar ratio of Zn to Cu2O is (0.5~3.0):1; (5-3) While stirring at 20-50℃, slowly add monoethanolamine or diethanolamine, wherein the molar ratio of Zn to amine is 1:(1-2), and then add deionized water, wherein the molar ratio of deionized water to Zn is (4-10):1; (5-4) Continue stirring the reaction for 4-12 hours. Zinc acid hydrolyzes and condenses on the surface of Cu2O to form a ZnO gel layer. Centrifuge, wash and dry to obtain ZnO gel-coated powder. (5-5) Under nitrogen protection, the powder coated with ZnO gel in step (5-4) is heat-treated at 120-150℃ for 1-2 hours to obtain cuprous oxide core-shell composite material.
[0044] When the shell is zinc oxide, zinc oxide is coated onto the surface of nano-cuprous oxide using an alcohol-phase sol-gel method. This alcohol-phase sol-gel method avoids the drawbacks of the strongly alkaline aqueous phase and high-temperature reaction in existing technologies. It not only provides milder reaction conditions and forms a more uniform and dense shell, but also allows the ZnO shell to synergistically exert antibacterial effects with Cu₂O, enhancing the material's performance in PBS. 2+ The release rate is reduced, and the antibacterial durability is significantly improved.
[0045] In step (5-1), the solvent may be anhydrous ethanol, and the concentration of nano-cuprous oxide in the dispersion is 5-15 g / L.
[0046] In step (5-2), the molar ratio of Zn to Cu2O is (0.5~3.0):1, including but not limited to any value or any two values from 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1, and 3:1. This ratio range can control the ZnO shell thickness between 4 and 15 nm. When the molar ratio of Zn to Cu2O is (0.5~3.0):1, it can ensure that Zn... 2+ A continuous and dense ZnO gel layer is formed by uniform hydrolysis and condensation on the Cu2O surface with sufficient supersaturation. After low-temperature heat treatment, a complete, pinhole-free ZnO shell is obtained. If the Zn ratio is too low (e.g., below 0.5:1), the amount of ZnO generated is insufficient to cover the entire core surface, resulting in a discontinuous shell and low coverage. If the Zn ratio is too high (e.g., above 3.0:1), the hydrolysis and condensation reaction is too vigorous, easily producing free ZnO aggregates or an excessively thick shell, affecting the exposure of the active sites in the core. The ZnO shell can synergistically exert antibacterial effects with Cu2O, allowing the composite material to exhibit Cu... 2+ The release rate is significantly reduced, and the antibacterial durability is improved.
[0047] In step (5-3), monoethanolamine or diethanolamine is used as a stabilizer, and the molar ratio of Zn to amine is 1:(1-2), for example, 1:1, 1:1.5, 1:2, etc.; the molar ratio of deionized water to Zn is (4-10):1, for example, 4:1, 6:1, 8:1, 10:1. The alcohol phase system avoids the oxidation risk of Cu2O in the aqueous phase, and the amine stabilizer can control the generation rate of Zn(OH)2 and avoid explosive precipitation.
[0048] In step (5-5), the heat treatment temperature can be, for example, 120℃, 135℃, or 150℃, and the time can be, for example, 1h, 1.5h, or 2h. Low-temperature heat treatment can transform the ZnO gel into a crystalline state while avoiding core oxidation.
[0049] When the shell is titanium dioxide, the preparation method of the nano-cuprous oxide core-shell composite material includes the following steps: (6-1) Disperse nano-cuprous oxide in a solvent to form a dispersion; (6-2) Add tetrabutyl titanate to the dispersion in step (6-1) so that the molar ratio of Ti to Cu2O is (0.5~3.0):1; (6-3) While stirring at 20-50℃, slowly add deionized water and dilute nitric acid, wherein the molar ratio of deionized water to Ti is (2-6):1, and the pH is adjusted to 3-4 by the dilute nitric acid; (6-4) Continue stirring the reaction for 8-24 hours. Tetrabutyl titanate hydrolyzes and condenses to form a TiO2 gel layer on the Cu2O surface. Centrifuge, wash, and vacuum dry. (6-5) Heat treatment at 120-150℃ for 1-2 hours under nitrogen atmosphere to obtain cuprous oxide core-shell composite material.
[0050] When the shell is titanium dioxide, the controllable hydrolysis under mild acidic conditions in the preparation method described above solves the strong alkalinity defect of traditional TiO2 coating. The TiO2 shell can absorb ultraviolet light below 400 nm, avoiding photocatalytic oxidation of Cu2O under light irradiation, and expanding the application of the composite material in the field of ultraviolet photocatalysis. In step (6-1), the solvent can be anhydrous ethanol, for example, and the concentration of nano-cuprous oxide in the dispersion is 5-15 g / L.
[0051] In step (6-2), the molar ratio of Ti to Cu2O is (0.5~3.0):1, including but not limited to any value or any two values from 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1, and 3:1. This ratio range can control the thickness of the TiO2 shell to be between 3 and 15 nm. Specifically, within this ratio range, it can be ensured that tetrabutyl titanate undergoes uniform hydrolysis and condensation on the Cu2O surface with sufficient supersaturation to form a continuous and dense TiO2 gel layer. After low-temperature heat treatment, a complete and pinhole-free TiO2 shell layer is obtained. If the Ti ratio is too low (e.g., below 0.5:1), the amount of TiO2 generated by hydrolysis is insufficient to cover the entire core surface, resulting in an extremely thin shell layer and incomplete coverage. If the Ti ratio is too high (e.g., above 3.0:1), the hydrolysis and condensation reaction is too vigorous, easily producing free TiO2 aggregates or an excessively thick shell layer, affecting the exposure of the active sites in the core. The TiO2 shell can absorb ultraviolet light below 400 nm, preventing Cu2O from undergoing photocatalytic oxidation under light conditions, and at the same time expanding the application of composite materials in the field of ultraviolet photocatalysis.
[0052] In step (6-3), the molar ratio of deionized water to Ti is (2-6):1, for example, it can be 2:1, 3:1, 4:1, 5:1, 6:1, etc. Dilute nitric acid is used to adjust the pH to 3-4. Dilute nitric acid can be used as a catalyst to control the hydrolysis rate of tetrabutyl titanate and avoid rapid hydrolysis to produce agglomerated TiO2 particles.
[0053] In step (6-5), the heat treatment temperature can be selected from, for example, 120℃, 135℃, or 150℃, and the time can be selected from, for example, 1h, 1.5h, or 2h. Low-temperature heat treatment can transform TiO2 gel into amorphous or anatase type while avoiding core oxidation.
[0054] In the preparation method of the cuprous oxide core-shell composite material of the present invention, the nano-cuprous oxide used can be conventional nano-cuprous oxide in the art, that is, it can be prepared by conventional known methods in the art or directly purchased. Preferably, the nano-cuprous oxide used in the present invention is self-made, and the specific preparation method includes the following steps: A copper salt and an organic ligand were dissolved in a solvent to prepare a copper salt mixed solution; the concentration of the organic ligand in the copper salt mixed solution was 1~100 mmol / L. A reducing agent and a pH adjuster are dissolved in a solvent to prepare a reducing precipitant solution; Under an inert atmosphere, a copper salt mixed solution and a reducing precipitant solution are synchronously and continuously injected into an ultrasonic-assisted microchannel reactor through independent microchannels. The volume flow ratio of the copper salt mixed solution to the reducing precipitant solution is controlled at 1:(0.5~1.5), the reaction temperature is 20-80℃, the ultrasonic frequency is 20~40 kHz, the ultrasonic power density is 50~500 W / L, and the residence time is 1~10 min to obtain a nano-cuprous oxide suspension. The obtained nano-cuprous oxide suspension was post-treated to obtain nano-cuprous oxide.
[0055] In the preparation method of the nano-cuprous oxide, the ultrasonic-assisted microchannel reactor used is the ultrasonic microfluidic nano-disperser of Moge Microfluidics Technology (Shantou) Co., Ltd. The reactor is also patented, and the corresponding patent information is: patent number CN118477590B, invention name is an ultrasonic continuous flow direct action dispersion device.
[0056] In the method for preparing nano-cuprous oxide, the concentration of the organic ligand in the copper salt mixed solution can be any value or a range of any two of the following: 1 mmol / L, 2 mmol / L, 10 mmol / L, 50 mmol / L, and 100 mmol / L. Preferably, the concentration of the organic ligand is 2–50 mmol / L. When the concentration of the organic ligand is 2–50 mmol / L, sufficient surface coverage is provided to prevent aggregation without excessive end-capping that would inhibit crystal growth.
[0057] In the method for preparing nano-cuprous oxide, the concentration of divalent copper salt in the copper salt mixed solution is 1~1000 mmol / L. The concentration of divalent copper salt can be any selection from 1 mmol / L, 5 mmol / L, 10 mmol / L, 17 mmol / L, 20 mmol / L, 50 mmol / L, 100 mmol / L, 200 mmol / L, 500 mmol / L, 1000 mmol / L, or any range of two of these concentrations.
[0058] In the method for preparing nano-cuprous oxide, the concentration of the reducing agent in the reducing precipitant solution is 1~750 mmol / L. In this method, the reduction potential and exothermic reaction are precisely controlled by adjusting the molar ratio of the reducing agent to copper ions; too low a concentration of the reducing agent will lead to incomplete reduction and residual Cu. 2+ The concentration of the reducing agent affects purity; excessively high concentrations can lead to abnormal grain growth or phase transformation due to intense exothermic reactions. Through experimentation, the inventors of this application have discovered that a reducing agent concentration range of 1-750 mmol / L can ensure the purity of Cu. 2+ Completely reduced to Cu +Simultaneously, mild reaction kinetics are maintained, thereby stably obtaining high-purity cubic phase and D 50 Controllable nano-cuprous oxide. The concentration of the reducing agent includes, for example, but is not limited to, any selection from 1 mmol / L, 5 mmol / L, 10 mmol / L, 50 mmol / L, 100 mmol / L, 170 mmol / L, 200 mmol / L, 300 mmol / L, 500 mmol / L, 750 mmol / L, or a range of any two of these concentrations.
[0059] In the reducing precipitant solution, the concentration of the pH adjuster is 100-800 mmol / L, for example, including but not limited to any selection or range formed by any two of the following concentrations: 100 mmol / L, 200 mmol / L, 300 mmol / L, 400 mmol / L, 500 mmol / L, 600 mmol / L, 700 mmol / L, and 800 mmol / L. Preferably, the concentration of the pH adjuster in the reducing precipitant solution is 400 mmol / L.
[0060] In the preparation method of the nano-cuprous oxide, the selection of the divalent copper salt is not particularly limited, and conventional divalent copper salts in the art can be used, such as at least one of copper sulfate, copper chloride, copper nitrate, and copper acetate.
[0061] In the preparation method of the nano-cuprous oxide, the reducing agent is selected from at least one of glucose, ascorbic acid, and sodium borohydride; In the preparation method of the nano-cuprous oxide, the pH adjuster is selected from at least one of NaOH, KOH, NaHCO3, and ammonia water.
[0062] Preferably, in the method for preparing nano-cuprous oxide, the reaction temperature is 60-80℃. A reaction temperature of 60-80℃ balances reaction rate and thermodynamic stability, avoiding the oxidation of Cu₂O to CuO due to excessively high temperatures or incomplete reaction due to excessively low temperatures, thereby obtaining D₂O within the optimal reaction process. 50 Smaller, narrower distribution, and better crystallinity of nano-cuprous oxide.
[0063] In the method for preparing nano-cuprous oxide, the hydraulic diameters of the microchannels for injecting the copper salt mixed solution and the reducing precipitant solution are each independently 0.5~2 mm. Specifically, the hydraulic diameter of the microchannel can be any selection from 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, and 2.0 mm, or any combination of any two of these values. Selecting a hydraulic diameter of 0.5~2 mm ensures that the fluid is in a laminar flow state to achieve microscopic uniform mixing, while avoiding the problems of nanoparticle blockage and high back pressure caused by excessively small microchannels. It also overcomes the defects of uneven mixing in conventional large channels. In other words, this size range allows the reactants to form a stable laminar shear and mass transfer environment within the channel, thereby achieving controllable, stable, and scalable synthesis of nanoparticles in a continuous flow mode.
[0064] In the preparation method of the nano-cuprous oxide, the microchannel reactor used is a continuous flow microchannel reactor, and the material of the microchannel can be selected from any one of stainless steel, titanium alloy, glass, polytetrafluoroethylene, and polyetheretherketone.
[0065] The solvents in the copper salt mixed solution and the reducing precipitant solution can each be water or a mixture of water and alcohol. When the solvent is a mixture of water and alcohol, the volume ratio of water to alcohol can be (1:10):(1-5). Specifically, the volume ratio of water to alcohol can be any selection from 10:1, 5:1, 2:1, 1:1, 1:2, 1:5, or any range of any two of these ratios. The alcohol can be selected from methanol, ethanol, ethylene glycol, glycerol, and isopropanol.
[0066] The inert atmosphere can be selected from any one of nitrogen, argon, and helium.
[0067] In the method for preparing nano-cuprous oxide, the nano-cuprous oxide suspension undergoes post-treatment, which includes, but is not limited to, cooling, centrifugation, washing, and vacuum drying. The centrifugation speed is 3000-12000 rpm, specifically, any selection from 3000 rpm, 5000 rpm, 8000 rpm, 10000 rpm, and 12000 rpm, or any combination of these speeds. The vacuum drying temperature is 40-80℃, and the vacuum drying time is 6-24 hours. Specifically, the vacuum drying temperature is any selection from 40℃, 50℃, 60℃, 70℃, and 80℃, or any combination of these speeds. The vacuum drying time is any selection from 6 hours, 8 hours, 12 hours, 16 hours, and 24 hours, or any combination of these speeds.
[0068] Finally, this invention also provides the application of the cuprous oxide core-shell composite material described above in antibacterial materials, photocatalytic materials, or gas sensing materials. The cuprous oxide core-shell composite material of this invention, due to the continuous and dense shell covering the core, maintains the activity of the cuprous oxide nanoparticles in the core, and the shell provides long-term stability. Therefore, the cuprous oxide core-shell composite material of this invention exhibits excellent long-lasting antibacterial properties and can be widely used in the preparation of antibacterial materials, photocatalytic materials, or gas sensing materials.
[0069] Furthermore, the application of the cuprous oxide core-shell composite material in antibacterial materials, photocatalytic materials, or gas sensing materials includes the preparation of synthetic fibers, thermoplastic polymers, antibacterial coatings, and aqueous antibacterial dispersions; for example, it can be added to nylon (PA) and polyester (PET) chips for melt spinning to prepare clothing or home textiles with antibacterial functions; it can be added to resins such as PE, PP, PVC, PLA, PC, and ABS by blending or masterbatch method to produce antibacterial injection molded parts, extruded pipes, films, or packaging materials; it can be dispersed in industrial circulating cooling water, central air conditioning cooling water, or landscape water bodies to inhibit the growth of bacteria and algae; and it can be formulated into aqueous or solvent-based coating agents and padding solutions for antibacterial and antifungal treatment of fabrics, leather, and building materials.
[0070] Applications in photocatalytic materials include the preparation of visible light-responsive photodegradation catalysts and photocatalytic reduction catalysts, for the degradation of organic pollutants, photocatalytic water splitting for hydrogen production, and photocatalytic reduction of carbon dioxide. Applications in gas sensing materials include the preparation of gas sensor sensitive elements and gas sensor sensitive films, for the fabrication of gas sensors for detecting formaldehyde, ethanol, ammonia, hydrogen sulfide, VOCs, etc., and as working electrode modification materials for the fabrication of electrochemical sensors for the electrochemical detection of glucose, dopamine, heavy metal ions, etc.
[0071] The cuprous oxide core-shell composite material of this invention achieves efficient physical isolation and chemical protection of the core by coating a nano-cuprous oxide core with a continuous and dense shell layer with a thickness of 1-50 nm. The shell layer material is selected from at least one of polydopamine, silica, alumina, zinc oxide, and titanium dioxide. This structure effectively blocks the direct contact between oxygen and moisture and the active core, significantly improving the material's oxidation resistance in room temperature air. Tests show that it can be stored at room temperature air for six months without the appearance of CuO characteristic peaks, and its color remains stable orange-yellow. Furthermore, because the shell layer thickness is controllable and continuous without pinholes, it provides long-term stability while retaining sufficient active sites, enabling the material to exhibit excellent comprehensive performance in antibacterial, photocatalytic, and gas sensing fields, thus solving the problems of easy oxidation and deactivation of nano-cuprous oxide and short functional lifespan.
[0072] The preparation method of the cuprous oxide core-shell composite material described in this invention provides multiple low-temperature coating process routes (method AF) to complete the construction of the core-shell structure at a temperature not exceeding 150°C, avoiding the damage to the nano-cuprous oxide lattice, surface ligands, and intrinsic activity caused by high-temperature calcination. Each method employs different shell materials, including in-situ polymerization of polydopamine, polydopamine-induced silica growth, atomic layer deposition of alumina, and metal oxide sol-gel coating under alcohol phase or near-neutral conditions. This ensures mild reaction conditions, high compatibility with the sensitive Cu2O core, and precise control of shell thickness and density. By controlling the precursor concentration, pH value, dropping rate, and reaction time, the generation of free particles and localized burst nucleation are effectively suppressed. The resulting core-shell material has a continuous and uniform shell without pinhole defects, good batch repeatability, and is suitable for large-scale production. This fundamentally overcomes the technical difficulties of strong alkali and high temperature causing core oxidation and structural instability in traditional coating processes. Attached Figure Description
[0073] Figure 1 This is a SEM image of a self-made nano-cuprous oxide according to the present invention.
[0074] Figure 2 for Figure 1 The image shows a histogram illustrating the particle size distribution of the self-made nano-cuprous oxide.
[0075] Figure 3 for Figure 1 The particle size distribution (DLS) of the self-made nano-cuprous oxide is shown.
[0076] Figure 4 for Figure 1 The XRD pattern of the self-made nano-cuprous oxide is shown.
[0077] Figure 5 for Figure 1 The image shows a comparison of the self-made nano cuprous oxide before and after storage for 6 months.
[0078] Figure 6 This is a SEM image of another self-made nano-cuprous oxide according to the present invention.
[0079] Figure 7 This is a transmission electron microscope (TEM) image of the cuprous oxide core-shell composite material described in Example 2A of the present invention.
[0080] Figure 8 This is a transmission electron microscope (TEM) image of the cuprous oxide core-shell composite material described in Comparative Example 2E of the present invention. Figure 9 This is for Embodiment 2A of the present invention (and) Figure 1 Energy dispersive X-ray spectroscopy (EDS) surface scan of the cuprous oxide core-shell composite material (for the same sample). Detailed Implementation
[0081] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0082] All raw materials used in the following examples are substances that can be obtained by conventional preparation methods or conventional channels in the art.
[0083] The ultrasonic-assisted microchannel reactor used in the preparation of the following nano-cuprous oxide is the ultrasonic microfluidic nanodispersant of Moge Microfluidics Technology (Shantou) Co., Ltd. The ultrasonic microfluidic nanodispersant is a commercially available device that can be purchased from Moge Microfluidics Technology (Shantou) Co., Ltd.
[0084] Nano-cuprous oxide 1: Self-made, the specific preparation method is as follows: (1) Weigh CuSO4·5H2O and Poloxamer 407, dissolve them in 200mL of a mixed solvent of deionized water and ethylene glycol (volume ratio of deionized water and ethylene glycol 1:1), stir to dissolve, so that the concentration of copper ions is 17mmol / L and the concentration of Poloxamer 407 is 2mmol / L, and a copper salt mixed solution is obtained. (2) Weigh NaOH and ascorbic acid, dissolve them in 50 mL of deionized water, stir to dissolve, so that the concentration of NaOH is 400 mmol / L and the concentration of ascorbic acid is 170 mmol / L, and obtain a reducing precipitant solution; (3) Under an inert atmosphere protected by N2 gas, the copper salt mixed solution from step (1) and the reducing precipitant solution from step (2) are simultaneously pumped into an ultrasonic-assisted microchannel reactor through independent microchannels at a volume flow ratio of 1:1 (10 mL / min each). The ultrasonic-assisted microchannel reactor has a microchannel hydraulic diameter of 1 mm, a reactor volume of 10 mL, an ultrasonic frequency of 28 kHz, an ultrasonic power density of 200 W / L, a reaction temperature of 70 °C, and a residence time of 1 min. Orange-red suspension is continuously collected at the reactor outlet, which is the nano-cuprous oxide suspension. (4) After cooling the nano-cuprous oxide suspension obtained in step (3), centrifuge at 8000 rpm for 10 min, discard the supernatant, and wash the precipitate three times each with deionized water and anhydrous ethanol. The washed product is dried in a vacuum drying oven at 60℃ for 12 h to obtain an orange-red powder product, which is nano-cuprous oxide 1.
[0085] The morphology, average particle size, and particle size distribution of nano-cuprous oxide 1 were tested using SEM (scanning electron microscopy). The specific testing methods are as follows: (1) Sample pretreatment: Disperse the cuprous oxide powder obtained by final drying in anhydrous ethanol, and sonicate for 5-10 min to initially disperse the aggregates; use a pipette to take 1-2 drops of suspension and drop them onto the conductive adhesive substrate, dry at room temperature and then spray gold with a thickness of 5-10 nm. (2) Imaging was performed using an accelerating voltage of 10kV, a working distance of 10mm, and a high vacuum mode. (3) Select at least 3 different fields of view to take SEM photos, each field of view containing ≥50 particles, and observe the particle morphology; ImageJ was used to measure the particle size of each particle in the SEM images (based on the equivalent circle diameter, i.e., the diameter of a circle with the same area as the particle); ≥200 particles were counted for each sample, and then sorted by particle size from smallest to largest for calculation. The cumulative percentage of 10% corresponds to a particle size of D. 10 ; The particle size corresponding to a cumulative proportion of 50% is D. 50 (Average particle size); The cumulative proportion of 90% corresponds to a particle size of D. 90 .
[0086] The obtained nano-cuprous oxide 1 has a uniform spherical morphology, without agglomeration, and an average particle size D. 50 It is 52nm, D 90 / D 10 It is 1.32.
[0087] SEM images of nano-cuprous oxide 1 are attached. Figure 1 As shown in the attached bar chart, the particle size distribution is statistically significant. Figure 2 As shown, its particle size distribution (DLS) is attached. Figure 3 As shown. (Attached) Figure 3 This is a particle size distribution diagram of DLS, used to illustrate that the product can form a stable dispersion system with a single peak and low polydispersity index in the aqueous phase, as shown by the attached... Figure 3 As can be seen, the product exhibits a unimodal distribution in the aqueous phase, with a polydispersity index (PDI) of 0.192, indicating good dispersion stability of the system. It should be noted that DLS characterizes the hydration kinetic diameter including the solvation layer, and its value is usually larger than the dry primary particle size measured by SEM. The difference between the two is common knowledge in the field and does not affect the determination of the actual particle size and ultrafine characteristics of the product.
[0088] The specific surface area of nano-cuprous oxide 1 was measured using BET, and the result was 32.5 m². 2 / g.
[0089] Nano-cuprous oxide 2: Self-made, the specific preparation method is as follows: (1) Same as step (1) of nano-cuprous oxide 1; (2) Same as step (2) of nano-cuprous oxide 1; (3) Under an inert atmosphere protected by N2 gas, the copper salt mixed solution from step (1) and the reducing precipitant solution from step (2) are simultaneously pumped into an ultrasonic-assisted microchannel reactor through independent microchannels at a volume flow ratio of 1:1 (10 mL / min each). The ultrasonic-assisted microchannel reactor has a microchannel hydraulic diameter of 1 mm, a reactor volume of 10 mL, an ultrasonic frequency of 28 kHz, an ultrasonic power of 200 W (ultrasonic power density is 200 W / L based on reactor volume), a reaction temperature of 25 °C (room temperature), a residence time of 1 min, and continuously collects orange-red suspension at the reactor outlet, which is the nano-cuprous oxide suspension. (4) After cooling the nano-cuprous oxide suspension obtained in step (3), centrifuge at 8000 rpm for 10 min, discard the supernatant, and wash the precipitate three times each with deionized water and anhydrous ethanol. The washed product is dried in a vacuum drying oven at 60℃ for 12 h to obtain an orange-red powder product, which is nano-cuprous oxide 2.
[0090] The same SEM (scanning electron microscopy) method was used to test nano-cuprous oxide 1. Nano-cuprous oxide 2 was tested and found to have a uniform spherical morphology, without agglomeration, and an average particle size (D). 50 ) is 100 nm, D 90 / D 10 It is 2.61.
[0091] Nano-cuprous oxide 3: Self-made, the specific preparation method is as follows: (1) Weigh CuSO4·5H2O and sodium citrate, dissolve them in 200mL of a mixed solvent of deionized water and ethylene glycol (the volume ratio of deionized water and ethylene glycol is 1:1), stir to dissolve, so that the copper ion concentration is 17mmol / L and the sodium citrate concentration is about 20mmol / L, and a copper salt mixed solution is obtained. (2) Same as step (2) of nano-cuprous oxide 1; (3) Same as step (3) of nano-cuprous oxide 1; (4) Same as step (4) of nano-cuprous oxide 1.
[0092] The same SEM (scanning electron microscopy) method was used to test nano-cuprous oxide 1. Nano-cuprous oxide 3 was tested and found to have a polyhedral morphology, no agglomeration, and an average particle size (D). 50 ) is 45nm, D 90 / D 10 It is 3.70.
[0093] Nano-cuprous oxide 4: Self-made, the specific preparation method is as follows: (1) Weigh CuSO4·5H2O and PVP, dissolve them in 200mL of a mixed solvent of deionized water and ethylene glycol (volume ratio of deionized water and ethylene glycol 1:1), stir to dissolve, so that the concentration of copper ions is 1mmol / L and the concentration of PVP is 100mmol / L, and obtain a copper salt mixed solution. (2) Weigh KOH and glucose, dissolve them in 50 mL of deionized water, stir to dissolve, so that the concentration of KOH is 400 mmol / L and the concentration of glucose is 750 mmol / L, and obtain a reducing precipitant solution; (3) Under an inert atmosphere protected by N2 gas, the copper salt mixed solution from step (1) and the reducing precipitant solution from step (2) are simultaneously pumped into an ultrasonic-assisted microchannel reactor through independent microchannels at a volume flow ratio of 1:0.5 (the flow rate of the copper salt mixed solution is 10 mL / min and the flow rate of the reducing precipitant solution is 5 mL / min). The ultrasonic-assisted microchannel reactor has a microchannel hydraulic diameter of 0.5 mm, a reactor volume of 10 mL, an ultrasonic frequency of 40 kHz, an ultrasonic power density of 500 W / L, a reaction temperature of 20 °C, and a residence time of 10 min. Orange-red suspension is continuously collected at the reactor outlet, which is the nano-cuprous oxide suspension. After cooling the nano-cuprous oxide suspension obtained in step (3), centrifuge at 3000 rpm for 10 min, discard the supernatant, and wash the precipitate three times each with deionized water and anhydrous ethanol. The washed product is dried in a vacuum drying oven at 40℃ for 24 h to obtain an orange-red powder product, which is nano-cuprous oxide 4.
[0094] The same SEM (scanning electron microscopy) method was used to test the nano-cuprous oxide 4 as for nano-cuprous oxide 1. The nano-cuprous oxide 4 exhibited a uniform spherical morphology, without agglomeration, and an average particle size (D). 50 ) is 78 nm, D 90 / D 10 The value is 2.67. The SEM image of nano-cuprous oxide 4 is attached. Figure 4 As shown.
[0095] Nano-cuprous oxide 5: Self-made, the specific preparation method is as follows: (1) Weigh CuSO4·5H2O and sodium citrate, dissolve them in 200mL of a mixed solvent of deionized water and ethylene glycol (volume ratio of deionized water and ethylene glycol 1:1), stir to dissolve, so that the concentration of copper ions is 100 mmol / L and the concentration of sodium citrate is 1mmol / L, and a copper salt mixed solution is obtained. (2) Weigh ammonia and sodium borohydride, dissolve them in 50 mL of deionized water, stir to dissolve, so that the concentration of ammonia is 400 mmol / L and the concentration of sodium borohydride is 1 mmol / L, and obtain a reducing precipitant solution. (3) Under an inert atmosphere protected by N2 gas, the copper salt mixed solution from step (1) and the reducing precipitant solution from step (2) are simultaneously pumped into an ultrasonic-assisted microchannel reactor through independent microchannels at a volume flow ratio of 1:1.5 (the flow rate of the copper salt mixed solution is 10 mL / min and the flow rate of the reducing precipitant solution is 15 mL / min). The ultrasonic-assisted microchannel reactor has a microchannel hydraulic diameter of 2 mm, a reactor volume of 10 mL, an ultrasonic frequency of 20 kHz, an ultrasonic power density of 50 W / L, a reaction temperature controlled at 80 °C, and a residence time of 5 min. Orange-red suspension is continuously collected at the reactor outlet, which is the nano-cuprous oxide suspension. (4) After cooling the nano-cuprous oxide suspension obtained in step (3), centrifuge at 12000 rpm for 3 min, discard the supernatant, and wash the precipitate three times each with deionized water and anhydrous ethanol. The washed product is dried in a vacuum drying oven at 80℃ for 6 h to obtain an orange-red powder product, which is nano-cuprous oxide 5.
[0096] The same SEM (scanning electron microscopy) method was used to test the nano-cuprous oxide 5 as for nano-cuprous oxide 1. The nano-cuprous oxide 5 exhibited a uniform spherical morphology, without agglomeration, and an average particle size (D...). 50 ) is 24nm, D 90 / D 10 It is 2.58.
[0097] Nano-cuprous oxide 6: Purchased from Zhejiang Manli Nanotechnology Co., Ltd., product model ML-Cu2O-N100, average particle size (D 50 ) is 100 nm Examples 1A-1I and Comparative Examples 1A-1C Examples 1A-1I and Comparative Examples 1A-1C of the present invention, which use polydopamine as the shell layer of the cuprous oxide core-shell composite material, are identical in preparation methods for the cuprous oxide core-shell composite materials of Examples 1A-1I and Comparative Examples 1A-1C, except for differences in some raw material ratios and process parameters. The specific raw material ratios and process parameters of Examples 1A-1I and Comparative Examples 1A-1C are shown in Table 1, and the specific steps are as follows: (1-1) The nano-cuprous oxide was uniformly dispersed in Tris buffer solution with pH 8 to form a premix solution, wherein the concentration of the nano-cuprous oxide in the premix solution was 5 g / L. (1-2) Add dopamine hydrochloride to the premix formed in step (1-1); (1-3) The reaction was stirred for a period of time under a certain temperature in a N2 atmosphere to obtain the initial product of cuprous oxide core-shell composite material; (1-4) The initial product of cuprous oxide core-shell composite material obtained in step (1-3) is centrifuged, washed and vacuum dried at 50°C to obtain cuprous oxide core-shell composite material.
[0098] Table 1. Selection of preparation methods for Examples 1A-1I and Comparative Examples 1A-1C
[0099] Examples 2A-2I and Comparative Examples 2A-2E Examples 2A-2I and Comparative Examples 2A-2E of the present invention describe cuprous oxide core-shell composite materials with a polydopamine and silica composite layer. The preparation methods for the cuprous oxide core-shell composite materials in Examples 2A-2I and Comparative Examples 2A-2E are identical except for some differences in raw material ratios and process parameters. The specific raw material ratios and process parameters for Examples 2A-2I and Comparative Examples 2A-2E are shown in Table 2, and the specific steps are as follows: (2-1) The nano-cuprous oxide is uniformly dispersed in a mixed solvent of water and ethanol (the volume ratio of water to ethanol is 1:1) to form a premixed solution, wherein the concentration of the nano-cuprous oxide in the premixed solution is 10 g / L. (2-2) Add dopamine hydrochloride to the premixed solution formed in step (2-1) and react at room temperature for 60 minutes to obtain an intermediate solution; (2-3) Add an ethanol solution of tetraethyl orthosilicate to the intermediate solution obtained in step (2-2), and react at a certain temperature for a period of time to obtain the initial product of cuprous oxide core-shell composite material; (2-4) The initial product of cuprous oxide core-shell composite material obtained in step (2-3) is centrifuged (10000 rpm, 10 min), washed 3 times each with deionized water and ethanol, and then vacuum dried at 50℃ for 12 h to obtain cuprous oxide core-shell composite material.
[0100] Table 2. Selection of preparation methods for Examples 2A-2I and Comparative Examples 2A-2E
[0101] Examples 3A-3I and Comparative Examples 3A-3D Examples 3A-3I and Comparative Examples 3A-3D of the present invention describe the cuprous oxide core-shell composite material with alumina as the shell layer. The preparation methods for the cuprous oxide core-shell composite materials in Examples 3A-3I and Comparative Examples 3A-3D are identical except for some differences in raw material ratios and process parameters. The specific raw material ratios and process parameters for Examples 3A-3I and Comparative Examples 3A-3D are shown in Table 3, and the specific steps are as follows: Using an atomic deposition apparatus, nano-cuprous oxide was placed in a reaction chamber, with trimethylaluminum and water as precursors, and deposition cycles were performed at a certain temperature (each cycle: TMA pulse 0.1 s, purge 30 s, H2O pulse 0.1 s, purge 30 s), to obtain a cuprous oxide core-shell composite material.
[0102] Table 3. Selection of preparation methods for Examples 3A-3I and Comparative Examples 3A-3D
[0103] Examples 4A-4I and Comparative Examples 4A-4D Examples 4A-4I and Comparative Examples 4A-4D of the present invention describe the cuprous oxide core-shell composite material with alumina as the shell layer. The preparation methods for the cuprous oxide core-shell composite materials in Examples 4A-4I and Comparative Examples 4A-4D are identical except for some differences in raw material ratios and process parameters. The specific raw material ratios and process parameters for Examples 4A-4I and Comparative Examples 4A-4D are shown in Table 4, and the specific steps are as follows: (4-1) Disperse nano-cuprous oxide in ethanol to form a dispersion, wherein the concentration of nano-cuprous oxide in the dispersion is 15 g / L; (4-2) Add an isopropanol solution of aluminum isopropoxide to the dispersion from step (4-1); (4-3) Under a certain temperature and N2 atmosphere, a pH adjuster is slowly added dropwise to adjust the pH to a certain range. When the pH adjuster is an alkaline solution, ammonia is used; when the pH adjuster is an acidic solution, hydrochloric acid is used. The dropping rate of the pH adjuster is controlled so that Al 3+ A uniform hydrolysis of Cu2O surface generates an Al(OH)3 gel layer; (4-4) Continue stirring for 5 hours, centrifuge, wash, and dry to obtain the Al(OH)3 coated intermediate; (4-5) The intermediate obtained in step (4-4) is heat-treated at a certain temperature under a nitrogen atmosphere for 2 hours to dehydrate Al(OH)3 and transform it into a continuous and dense amorphous Al2O3 shell, thus obtaining the cuprous oxide core-shell composite material.
[0104] Table 4. Selection of preparation methods for Examples 4A-4I and Comparative Examples 4A-4D
[0105] Examples 5A-5I and Comparative Examples 5A-5E Examples 5A-5I and Comparative Examples 5A-5E of the present invention, which use zinc oxide as the shell layer of the cuprous oxide core-shell composite material, are identical in preparation methods for the cuprous oxide core-shell composite materials of Examples 5A-5I and Comparative Examples 5A-5E, except for some differences in raw material ratios and process parameters. The specific raw material ratios and process parameters of Examples 5A-5I and Comparative Examples 5A-5E are shown in Table 5, and the specific steps are as follows: (5-1) Disperse nano-cuprous oxide in anhydrous ethanol to form a dispersion, wherein the concentration of nano-cuprous oxide in the dispersion is 10 g / L; (5-2) Add zinc acetate dihydrate to the dispersion in step (5-1); (5-3) While stirring at 20-50℃, slowly add diethanolamine, then add deionized water; (5-4) After stirring continuously for 8 hours, zinc acid hydrolyzes and condenses to form a ZnO gel layer on the Cu2O surface. After centrifugation, washing and drying, ZnO gel-coated powder is obtained. (5-5) Under nitrogen protection, the ZnO gel-coated powder from step (5-4) is heat-treated at a certain temperature for 2 hours to obtain cuprous oxide core-shell composite material.
[0106] Table 5. Selection of preparation methods for Examples 5A-5I and Comparative Examples 5A-5E
[0107] Examples 6A-6I and Comparative Examples 6A-6F Examples 6A-6I and Comparative Examples 6A-6F of the present invention, which use titanium dioxide as the shell layer of the cuprous oxide core-shell composite material, are identical in preparation methods for the cuprous oxide core-shell composite materials of Examples 6A-6I and Comparative Examples 6A-6F, except for some differences in raw material ratios and process parameters. The specific raw material ratios and process parameters of Examples 6A-6I and Comparative Examples 6A-6F are shown in Table 6, and the specific steps are as follows: (6-1) Disperse nano-cuprous oxide in anhydrous ethanol to form a dispersion, wherein the concentration of nano-cuprous oxide in the dispersion is 10 g / L; (6-2) Add tetrabutyl titanate to the dispersion in step (6-1); (6-3) Under a certain temperature and stirring, deionized water and dilute nitric acid are slowly added, wherein the pH is adjusted to a certain range by the dilute nitric acid; (6-4) Continue stirring for 10 hours. Tetrabutyl titanate hydrolyzes and condenses to form a TiO2 gel layer on the Cu2O surface. Centrifuge, wash, and vacuum dry. (6-5) Heat treatment at a certain temperature under a nitrogen atmosphere for 1-2 hours yields cuprous oxide core-shell composite material.
[0108] Table 6. Selection of preparation methods for Examples 6A-6I and Comparative Examples 6A-6F
[0109] Example 1 Transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDS) were performed on the cuprous oxide core-shell composite materials obtained in the above examples and comparative examples to test the morphology, size, interface clarity, and elemental distribution on the particles of each group of cuprous oxide core-shell composite materials. The specific results are shown in Tables 7-12 below, and the TEM and EDS results of some representative samples are attached. Figure 5-7 As shown.
[0110] Table 7. Morphology and dimensions of the core-shell composite materials of Examples 1A-1I and Comparative Examples 1A-1C
[0111] As shown in Table 7, when the shell is polydopamine, the cuprous oxide core-shell composite material prepared by the method described in this application has a clear core-shell structure, and the shell thickness is mainly distributed in the range of 5-12 nm. Specifically, in the dopamine single-shell system, the shell thickness increases with the increase of the dopamine hydrochloride feed ratio, from 5 nm at 1:1 to 12 nm at 3:1, confirming that the feed ratio is the key factor controlling the thickness of the polydopamine film. At the same time, a uniform coating of about 8 nm was achieved on the cores of different particle sizes and morphologies (Examples 1E-1H), demonstrating the good adaptability of this method to the core size. Comparative Example 1A resulted in a discontinuous shell due to an excessively low feed ratio (0.4:1), while Comparative Example 1B resulted in an excessively thick shell and the formation of free aggregates due to an excessively high feed ratio (4:1), indicating that the specific range of feed ratios described in this application can effectively balance the integrity of the coating and the exposure of the active sites in the core.
[0112] Table 8. Morphology and dimensions of the core-shell composite materials of Examples 2A-2I and Comparative Examples 2A-2E
[0113] The transmission electron microscope (TEM) image of the cuprous oxide core-shell composite material of Example 2A is attached. Figure 5 As shown, the TEM image of its comparative example 2E is attached. Figure 6 As shown. (From the appendix) Figure 5 It can be seen that the cuprous oxide core-shell composite material prepared in Example 2A has a complete core-shell structure, with a core diameter of approximately 50 nm and a total shell thickness of approximately 10 nm. The interface is clear, proving that the composite shell is uniformly coated, continuous, and free of pinholes. Furthermore, the attached... Figure 6It can be seen that the core lattice of the cuprous oxide core-shell composite material prepared in Comparative Example 2E is blurred, the CuO phase appears, and the interface is unclear.
[0114] The cuprous oxide core-shell composite material described in Example 2A (and) Figure 1 The energy-dispersive X-ray spectroscopy (EDS) surface scan of the same sample is attached. Figure 7 As shown, by appendix Figure 7 It can be seen that the distribution of Si elements completely coincides with the position of the shell, while Cu elements are concentrated in the core region, proving that the SiO2 shell successfully coats the Cu2O surface without element mixing, thus verifying the chemical integrity of the coating.
[0115] As shown in Table 8, when the shell is a composite layer of polydopamine and silica, the method of the present invention can prepare a cuprous oxide core-shell composite material with a clear core-shell structure and Cu concentrated in the core region. The shell thickness can be adjusted as needed within the range of 5-12 nm, and uniform coating can be achieved on cores of different particle sizes. In Examples 2A-2D, when the tetraethyl orthosilicate concentration increased from 1.0 M to 2.0 M, the shell thickness increased from about 8 nm to about 15 nm, indicating that the silicon source concentration is an effective process parameter for controlling the shell thickness. Meanwhile, in Examples 2E-2H with different core sizes, a complete core-shell structure with Cu concentrated in the core region was obtained, indicating that the method has good dimensional universality. In contrast, Comparative Example 2A had an extremely thin and discontinuous shell due to insufficient precursor concentration; Comparative Example 2B had an excessively thick shell due to the introduction of a large number of free SiO2 particles caused by excessively high concentration; Comparative Example 2C had local exposure due to uneven coating; and Comparative Example 2D had a severely uneven structure due to the formation of a large number of free clusters caused by excessively rapid solvent evaporation. Although Comparative Example 2E met the shell thickness standard, the high reaction temperature led to core oxidation and interface blurring.
[0116] Table 9. Morphology and dimensions of the core-shell composite materials of Examples 3A-3I and Comparative Example 3A-3D
[0117] As shown in Table 9, when the shell is made of alumina and prepared using atomic deposition, the resulting cuprous oxide core-shell composite material exhibits excellent morphological uniformity. The shell thickness is controllable within the range of 1.5–7.5 nm, and a smooth and dense coating can be achieved on cores of different particle sizes. Examples 3A–3D show that the shell thickness increases with the concentration of the shell precursor, from 1.5 nm to 7.5 nm. Examples 3E–3I further demonstrate that the preparation method has good universality for cores of different morphologies and sizes, maintaining a clear core-shell interface and concentrated Cu signal distribution. In contrast, Comparative Example 3A suffers from uneven shell and pinholes due to insufficient concentration; Comparative Example 3B suffers from core oxidation and interface blurring due to excessively high deposition temperature; Comparative Example 3C fails to provide effective protection due to its extremely thin shell; and Comparative Example 3D suffers from stress accumulation and cracking and peeling due to an excessively thick shell.
[0118] Table 10 Morphology and dimensions of the core-shell composite materials of Examples 4A-4I and Comparative Examples 4A-4D
[0119] As shown in Table 10, when the shell is alumina and prepared using a chemical deposition method, the resulting cuprous oxide core-shell composite material also exhibits a clear core-shell structure and a continuous, dense shell coating. The shell thickness can be adjusted as needed within the range of 5–15 nm. This method can achieve continuous and uniform coating on cores of different particle sizes. Examples 4A–4D show that when the molar ratio of Al to Cu₂O increases from 0.8:1 to 3.5:1, the shell thickness increases from approximately 5 nm to approximately 15 nm, verifying the direct control effect of the aluminum source feed amount on the shell thickness. When the molar ratio of Al to Cu₂O is ≥1.5:1, a continuous, dense, and pinhole-free Al₂O₃ shell can be obtained, demonstrating the saturated coating effect on the core surface under conditions of excess Al. Examples 4E–4I further demonstrate that the method has good universality for cores of different sizes and morphologies, maintaining a clear core-shell structure and a continuous shell distribution. In contrast, Comparative Example 4A suffered from core oxidation and interface blurring due to high reaction temperature; Comparative Example 4B suffered from incomplete shell and localized agglomeration due to low ambient pH; Comparative Example 4C suffered from core oxidation and impurity phases due to high ambient pH; and Comparative Example 4D suffered from uneven shell and free precipitates due to poor dispersion.
[0120] Table 11 Morphology and dimensions of the core-shell composite materials of Examples 5A-5I and Comparative Examples 5A-5E
[0121] As shown in Table 11, when the shell is zinc oxide, the method of the present invention can prepare a cuprous oxide core-shell composite material with a clear core-shell structure and uniform Zn distribution in the shell. The shell thickness can be adjusted as needed within the range of 4-15 nm. The method can achieve uniform and dense coating on cores of different particle sizes, and the Zn element is uniformly distributed in the shell. Examples 5A-5D show that when the molar ratio of Zn to Cu2O increases from 0.5:1 to 3.0:1, the shell thickness increases from about 5 nm to about 15 nm, verifying the direct control effect of the zinc source feed amount on the shell thickness. When the molar ratio of Zn to Cu2O is ≥1.2:1, a continuous, dense, and pinhole-free ZnO shell can be obtained, demonstrating the saturated coating effect on the core surface under Zn excess conditions. Examples 5E-5I further demonstrate that the preparation method has good universality for cores of different sizes and morphologies, maintaining a clear core-shell structure and a complete interface, with the Zn element uniformly distributed in the shell. In contrast, Comparative Example 5A had an excessively thick shell and free ZnO clusters due to excessively high concentration; Comparative Example 5B had an incomplete shell due to insufficient hydrolysis; Comparative Example 5C had an excessively thin shell and low coverage due to insufficient concentration; Comparative Example 5D had core oxidation and CuO impurities due to excessively high heat treatment temperature; and Comparative Example 5E had an amorphous shell due to excessively low heat treatment temperature and poor crystallinity.
[0122] Table 12 Morphology and dimensions of the core-shell composite materials of Examples 6A-6I and Comparative Example 6A-6F
[0123] As shown in Table 12, when the shell is titanium dioxide, the method of the present invention can prepare a cuprous oxide core-shell composite material with a clear core-shell structure and uniform Ti element distribution in the shell. The shell thickness can be adjusted as needed within the range of 3-15 nm. The method can achieve uniform and continuous coating on cores of different particle sizes. Examples 6A-6D show that when the molar ratio of Ti to Cu2O increases from 0.5:1 to 3.0:1, the shell thickness increases from about 4 nm to about 15 nm, verifying the direct control effect of the titanium source feed amount on the shell thickness. When the molar ratio of Ti to Cu2O is ≥1.2:1, a continuous, dense, and pinhole-free TiO2 shell can be obtained, demonstrating the saturated coating effect on the core surface under Ti excess conditions. Examples 6E-6I further demonstrate that the preparation method has good universality for cores of different sizes and morphologies, maintaining a clear core-shell structure and a complete interface, with Ti element uniformly distributed in the shell.
[0124] In contrast, Comparative Example 6A had an excessively thick shell and free TiO2 clusters due to excessively high concentration; Comparative Example 6B had an extremely thin shell and incomplete coating due to insufficient concentration; Comparative Example 6C had core oxidation due to excessively high reaction temperature; Comparative Example 6D had a rough shell and a large number of free particles due to unsuitable pH environment and excessively rapid hydrolysis; Comparative Example 6E had a loose and porous shell due to unsuitable pH environment and incomplete hydrolysis; and Comparative Example 6F had core oxidation due to excessively high heat treatment temperature.
[0125] Example 2 Long-term storage stability, antibacterial properties and thermal stability tests of the cuprous oxide core-shell composite material of this invention. The long-term storage stability and antibacterial properties of the cuprous oxide core-shell composite materials of Examples 1A, 2A, 3A, 4A, 5A, 6A and Comparative Examples 1A, 2E, 5D, and the original nano-cuprous oxide 1 were tested respectively. The test methods are as follows: Long-term storage stability: The sample was placed in room temperature air for 6 months, and the color change was observed and XRD analysis was performed.
[0126] Antibacterial properties: The antibacterial rate against Escherichia coli was tested using the plate count method.
[0127] The test results are shown in Table 13 below.
[0128]
[0129] As shown in Table 13, all samples from the examples maintained an orange-yellow color and showed no characteristic CuO peaks. In contrast, the comparative examples and the original Cu2O exhibited varying degrees of oxidation discoloration and impurity phase formation, demonstrating that the shell of this invention effectively blocks oxygen and moisture, achieving long-term stable storage. Regarding antibacterial performance, the examples maintained antibacterial rates above 98.5% due to the intact preservation of the core active sites; Example 5A achieved an antibacterial rate as high as 99.8% due to the synergistic effect of the ZnO shell. The comparative examples, due to shell defects or core oxidation, showed a significant decrease in antibacterial rate to below 85%.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A cuprous oxide core-shell composite material, characterized in that, The cuprous oxide core-shell composite material includes a core and a continuous, dense shell layer covering the surface of the core; The core is nano-cuprous oxide; The shell has a thickness of 1-50 nm and is composed of aluminum oxide. The average particle size of the nano-cuprous oxide is 20-180 nm, and the shell is formed under conditions not exceeding 150 °C and not strongly alkaline. The cuprous oxide core-shell composite material was prepared by the following method: (3-1) Using an atomic deposition apparatus, cuprous oxide nanoparticles are placed in a reaction chamber, and trimethylaluminum and water are used as precursors. Deposition is carried out for 10-50 cycles at 80-120°C to obtain a cuprous oxide core-shell composite material; or it can be prepared using the following methods: (4-1) Disperse nano-cuprous oxide in a solvent to form a dispersion; (4-2) Add aluminum isopropoxide solution in isopropanol to the dispersion in step (4-1) so that the molar ratio of Al to Cu2O is (0.5~4.0):1; (4-3) Under an inert atmosphere and at 20-50℃, slowly add an alkaline solution to adjust the pH to 6.5-7.5, controlling the dropping rate to 0.1-0.5 mL / min, so that Al 3+ A uniform hydrolysis of Cu2O surface generates an Al(OH)3 gel layer; (4-4) Continue stirring for 2-6 hours, centrifuge, wash, and dry to obtain the Al(OH)3 coated intermediate; (4-5) The intermediate obtained in step (4-4) is heat-treated at 120-150℃ for 1-2 hours under a nitrogen atmosphere to dehydrate Al(OH)3 and transform it into a continuous and dense amorphous Al2O3 shell, thus obtaining the cuprous oxide core-shell composite material.
2. The cuprous oxide core-shell composite material as described in claim 1, characterized in that, The surface of the nano-cuprous oxide has a modification layer formed by chemical modification with organic ligands, and the shell layer covers the modification layer of the nano-cuprous oxide, and the nano-cuprous oxide satisfies the following: D 90 / D 10 =1.2~5.0; The D 90 The particle size corresponding to a cumulative particle size distribution percentage of 90% for the aforementioned nano-cuprous oxide is defined as follows: The D 10 This refers to the particle size corresponding to a cumulative particle size distribution percentage of 10% for the nano-cuprous oxide.
3. The cuprous oxide core-shell composite material as described in claim 2, characterized in that, The organic ligand in the modified layer is selected from at least one of poloxamer, Tween, sodium citrate, PVP, SDS, and CTAB.
4. The cuprous oxide core-shell composite material as described in claim 2, characterized in that, The nano-cuprous oxide is composed of cubic phase Cu2O; And / or, the nano-cuprous oxide particles are spherical, near-spherical, or polyhedral; And / or, the specific surface area of the nano-cuprous oxide is 15~50 m². 2 / g; And / or, the nano-cuprous oxide, when stored at room temperature and in air for 6 months, shows no CuO characteristic peaks in XRD analysis and remains orange-red in color.
5. The method for preparing the cuprous oxide core-shell composite material according to any one of claims 1-4, characterized in that, The method includes the following steps: (3-1) Using an atomic deposition device, nano-cuprous oxide is placed in a reaction chamber, and trimethylaluminum and water are used as precursors. 10 to 50 cycles of deposition are carried out at 80 to 120°C to obtain cuprous oxide core-shell composite material. Alternatively, the method may include the following steps: (4-1) Disperse nano-cuprous oxide in a solvent to form a dispersion; (4-2) Add aluminum isopropoxide solution in isopropanol to the dispersion in step (4-1) so that the molar ratio of Al to Cu2O is (0.5~4.0):1; (4-3) Under an inert atmosphere and at 20-50℃, slowly add an alkaline solution to adjust the pH to 6.5-7.5, controlling the dropping rate to 0.1-0.5 mL / min, so that Al 3+ A uniform hydrolysis of Cu2O surface generates an Al(OH)3 gel layer; (4-4) Continue stirring for 2-6 hours, centrifuge, wash, and dry to obtain the Al(OH)3 coated intermediate; (4-5) The intermediate obtained in step (4-4) is heat-treated at 120-150℃ for 1-2 hours under a nitrogen atmosphere to dehydrate Al(OH)3 and transform it into a continuous and dense amorphous Al2O3 shell, thus obtaining the cuprous oxide core-shell composite material.
6. The method for preparing the cuprous oxide core-shell composite material as described in claim 5, characterized in that, The nano-cuprous oxide was prepared by the following method: A copper salt and an organic ligand were dissolved in a solvent to prepare a copper salt mixed solution; the concentration of the organic ligand in the copper salt mixed solution was 1~100 mmol / L. A reducing agent and a pH adjuster are dissolved in a solvent to prepare a reducing precipitant solution; Under an inert atmosphere, a copper salt mixed solution and a reducing precipitant solution are synchronously and continuously injected into an ultrasonic-assisted microchannel reactor through independent microchannels. The volume flow ratio of the copper salt mixed solution to the reducing precipitant solution is controlled at 1:(0.5~1.5), the reaction temperature is 20-80℃, the ultrasonic frequency is 20~40 kHz, the ultrasonic power density is 50~500 W / L, and the residence time is 1~10 min to obtain a nano-cuprous oxide suspension. The obtained nano-cuprous oxide suspension was post-treated to obtain nano-cuprous oxide.
7. The method for preparing the cuprous oxide core-shell composite material as described in claim 6, characterized in that, In the copper salt mixed solution, the concentration of divalent copper salt is 1~1000 mmol / L; And / or, in the reducing precipitant solution, the concentration of the reducing agent is 1~750 mmol / L; And / or, in the reducing precipitant solution, the concentration of the pH adjuster is 100-800 mmol / L; And / or, the divalent copper salt is selected from at least one of copper sulfate, copper chloride, copper nitrate, and copper acetate; And / or, the reducing agent is selected from at least one of glucose, ascorbic acid, and sodium borohydride; And / or, the pH adjuster is selected from at least one of NaOH, KOH, NaHCO3, and ammonia water; And / or, the hydraulic diameter of the microchannels for injecting the copper salt mixture solution and the reducing precipitant solution is independently 0.5~2 mm.
8. The application of the cuprous oxide core-shell composite material as described in any one of claims 1-4 in antibacterial materials, photocatalytic materials or gas sensing materials.
Citation Information
Patent Citations
Treatment method for improving stability of cuprous oxide
CN113929129A
An ultrasonic continuous flow direct action dispersion device
CN118477590B
Preparation method of red cuprous oxide pigment with core-shell structure
CN120737631A
Cuprous oxide-titanium dioxide composite structure and preparation method thereof
CN103949253A
Modified silicon dioxide coated cuprous oxide with core-shell structure and preparation method thereof
CN106833024A
